A rare non-Robertsonian translocation involving chromosomes 15 and 21 - Baruffi, Marcelo Razera; Souza, Deise Helena; Silva, Rosana Aparecida Bicudo; Ramos, Ester Silveira; Moretti-ferreira, Danilo (Associação Paulista de Medicina (APM), 2013)
CONTEXTO:Translocações robertsonianas (TR) estão entre os rearranjos estruturais balanceados mais comuns em humanos e compreendem a fusão da cromatina completa do braço longo de dois cromossomos acrocêntricos. No entanto, são raras as translocações não Robertsonianas envolvendo esses cromossomos.RELATO DE CASO:Nós descrevemos uma translocação não balanceada de novo envolvendo os cromossomos 15 e 21. A recém-nascida era filha de uma mãe de 29 anos e de um pai de 42 anos, casal não consanguíneo. Os achados clínicos levaram ao diagnóstico de síndrome de Down (SD) com defeitos cardíacos congênitos graves (persistência do canal arterial e defeito do septo atrioventricular completo), além de baixos comprimento e peso ao nascimento (< 5o e < 10o percentil em curvas de medidas específicas para SD, respectivamente). A análise citogenética convencional revelou o cariótipo 46,XX,der(15)(15pter→15q26.2

CONTEXT:Robertsonian translocations (RT) are among the most common balanced structural rearrangements in humans and comprise complete chromatin fusion of the long arm of two acrocentric chromosomes. Nevertheless, non-Robertsonian translocation involving these chromosomes is a rare event.CASE REPORT:We report a de novo unbalanced translocation involving chromosomes 15 and 21. The newborn was the daughter of a 29-year-old mother and a 42-year-old father. The couple was non-consanguineous. Clinical findings led to the diagnosis of Down syndrome (DS) with severe congenital heart defects (persistent arterial duct, and complete atrioventricular septal defect), as well as low birth length and weight (< 5th and < 10th percentile, respectively, based on specific measurement curves for DS). Conventional cytogenetic analysis revealed the karyotype 46,XX,der(15)(15pter→15q26.2
Uma rara translocacao nao robertsoniana envolvendo os cromossomos 15 e 21
Keywords: Translocacao genetica; Sindrome de Down; Cromossomos humanos par 15; Cromossomos humanos par 21; Delecao cromossomica; Translocation, genetic; Down syndrome; Chromosomes, human, pair 15; Chromosomes, human, pair 21; Chromosome deletion